Policing by social skills: the importance of empathy and appropriate emotional expressions in the recruitment, selection and education of Danish police officers - Bloksgaard, Lotte (Policing and society, 2021)
Motivated politically by an interest in a friendlier, more service-minded police force, the Danish police have changed profoundly in recent decades. With a relatively low crime rate, strong democratic traditions, and exceptionally high levels of trust in the police, Denmark offers an interesting case for examining how a service-minded police force is created. The ideal, professional Danish police officer is supposed to engage in equal dialogue with citizens. When recruiting and educating police officers, considerable emphasis is placed on assessing and developing social skills, empathy in particular. Analysing interviews, fieldwork and documents, focussing on recruitment, selection, education and the assessment of Danish police recruits, the article explores how the shift towards service-mindedness is sought achieved, as well as some of the challenges and tensions involved in pursuing this ideal. Theoretically, the analysis draws on Hochschild’s concepts of feeling rules and emotional labour together with Illouz’s perspectives on the demands for communicative and emotional skills in modern working life. These let us understand modern policing as regulated and performed through emotional and embodied practices.